K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

4 tháng 12 2016

2x+2-2x=768

=>2xx22-2x=768

=>2x(4-1)=768

=>2x=768:3=256

=>2x=28

=>x=8

4 tháng 3 2016

b, x = 10 , y = 8

20 tháng 10 2022

\(\Leftrightarrow4^{4x+5}-4^{4x+4}=768\)

\(\Leftrightarrow4^{4x+4}\left(4-1\right)=768\)

=>4^(4x+4)=256

=>4x+4=4

=>x=0

5 tháng 1 2017

(2x + 1) . (2x + 2) . (2x + 3) . (2x + 4) - 5y = 11879

[(2x + 1). (2x + 4)].[(2x + 2) . (2x + 3)] -5y = 11879

(4x2+10x+4).(4x2+10x+6) -5y = 11879

Đặt t= 4x2+10x+4

t(t+2) -5y = 11879

t2+2t-5y = 11879

(t+1)2 = 11880+5y

(4x2+10x+5)2 = 5(2376+y)

=> x = 0; y=-2371

5 tháng 1 2017

thanks

Bài 2: 

a: Ta có: \(2^{x+1}\cdot3^y=12^x\)

\(\Leftrightarrow2^{x+1}\cdot3^y=2^{2x}\cdot3^x\)

\(\Leftrightarrow\left\{{}\begin{matrix}x+1=2x\\x=y\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=1\\y=1\end{matrix}\right.\)

4 tháng 4 2023

\(a,3x^2-3x\left(x-2\right)=36\\ \Leftrightarrow3x^2-3x^2+6x=36\\ \Leftrightarrow6x=36\\ \Leftrightarrow x=6\\ b,5x\left(4x^2-2x+1\right)-2x\left(10x^2-5x+2\right)=-36\\ \Leftrightarrow20x^3-10x^2+5x-20x^3+10x^2-4x+36=0\\ \Leftrightarrow\left(20x^3-20x^3\right)+\left(-10x^2+10x^2\right)+\left(5x-4x\right)=-36\\ \Leftrightarrow x=-36\)

28 tháng 9 2015

1/ => 2x + 1 = 0 => 2x = -1 => x = -1/2

hoặc 3x - 9 = 0 => 3x = 9 => x = 3

Vậy x = { -1/2 ; 3 }

2/ => x2 = 0 => x = 0 

hoặc 2/3 - 5x = 0 => 5x = 2/3 => x = 2/15

Vậy x = 2/15 ; x = 0

3/ 2x - 7 = 7 - 2x

=> 2x + 2x = 7 + 7 

=> 4x = 14

=> x = 7/2

Vậy x = 7/2